Dilema Hukum Humaniter dan Peran Hukum Militer Dalam Menjaga Kedaulatan Negara Serta Melindungi Warga Sipil - Mawene, Marcha Jeanne; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This research examines the tension between the application of international humanitarian law and the legal needs of the military in maintaining state sovereignty during armed conflict. Using normative juridical methods, the study analyses the legal framework governing military action and the protection of civilians in conflict situations. The research focuses on three issues: the effectiveness of applying humanitarian law without compromising military strategies to safeguard sovereignty; obstacles in ensuring civilian protection and solutions from humanitarian law; and synergies between military law and humanitarian law without compromising operational effectiveness. The results show that the dilemma between military and humanitarian interests can be harmonised through proper interpretation of the principles of proportionality, distinction, and precaution, as well as the development of military doctrine that  integrates humanitarian values. The research concludes that strengthening compliance mechanisms, humanitarian law training for military personnel, and improving rules of engagement are crucial steps to balance military imperatives with humanitarian protection in contemporary armed conflicts.